Frequency and Stability of Chromosomal Integration of Adenovirus Vectors - Harui, Airi (American Society for Microbiology, 1999)
One of the limitations of adenovirus vectors is the lack of machinery necessary for their integration into host chromosomes, resulting in short-term gene expression in dividing cells. We analyzed frequencies of integration and persistence of gene expression from integrated adenovirus vectors. Both E1-substituted and helper-dependent adenovirus vectors achieved similar integration efficiencies of ∼10(−3) to 10(−5) per cell, with the helper-dependent vector showing slightly higher efficiencies. In stable cell pools, gene expression of the integrated vector persisted for at least 50 cell divisions without selection. However, some stable cell clones showed changes in gene expression, which were accompanied by structural changes in the integrated vector DNA.